2011
DOI: 10.3892/ijo.2011.973
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl sulfide induces cell cycle arrest and apoptosis in HeLa human cervical cancer cells through the p53, caspase- and mitochondria-dependent pathways

Abstract: Abstract. Diallyl sulfide (DAS), one of the main active constituents of garlic, causes growth inhibition of cancer cells in vitro and promotes immune responses in vivo in experimental settings. However, its effects on the induction of cell cycle and apoptosis in human cervical cancer cells are still unclear. The aims of this study were to explore the anti-cancer effects of DAS in HeLa human cervical cancer cells and to investigate the underlying mechanisms in vitro. Cytotoxicity and apoptosis in HeLa human cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Ample studies suggest that mitochondrial function is responsible for cell death and is considered a target for anticancer drugs [3133]. We confirm that LQ enhances the dissipation of Δ ψm in hepatocellular carcinoma cells.…”
Section: Discussionsupporting
confidence: 77%
“…Ample studies suggest that mitochondrial function is responsible for cell death and is considered a target for anticancer drugs [3133]. We confirm that LQ enhances the dissipation of Δ ψm in hepatocellular carcinoma cells.…”
Section: Discussionsupporting
confidence: 77%
“…NaHS also retards breast cancer cells transitioning from G1 to G0 phase and inhibits breast cancer cell division [ 35 ]. A 48 h treatment of diallyl sulfide induced G0/G1 cell cycle arrest in HeLa human cervical cancer cells [ 36 ]. These studies showed the potential ability of H 2 S to inhibit cell proliferation by regulating the cell cycle and hence DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In HeLa human cervical cancer cells, for example, treatment with DAS resulted in G 0 /G 1 cell cycle arrest and increased expression of pro-caspases [17]. In addition, DAS treatment was shown to enhance the cytosolic levels of mitochondrial enzyme cytochrome c and p53.…”
Section: Das: Anticancer Effectsmentioning
confidence: 99%